2000
DOI: 10.1152/ajpgi.2000.279.6.g1226
|View full text |Cite
|
Sign up to set email alerts
|

Opposing roles of K+and Clchannels in maintenance of opossum lower esophageal sphincter tone

Abstract: The ionic basis underlying the maintenance of myogenic tone of lower esophageal sphincter circular muscle (LES) was investigated in opossum with the use of standard isometric tension and conventional intracellular microelectrode recordings in vitro. In tension recording studies, nifedipine (1 microM) reduced basal tone to 27.7 +/- 3.8% of control. The K(+) channel blockers tetraethylammonium (TEA, 2 mM), charybdotoxin (100 nM), and 4-aminopyridine (4-AP, 2 mM) enhanced resting tone, whereas apamin and glibencl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 45 publications
3
34
2
Order By: Relevance
“…We speculate that in circular smooth muscle of the opossum LES, the activation of K Na channels may serve to stabilize the RMP. The basal tone of the LES is maintained by constant Ca ϩ influx via ongoing Ca 2ϩ action potentials (34), and the accumulated Ca 2ϩ is likely extruded from the cell via a Na ϩ /Ca 2ϩ exchanger (25). This, in turn, leads to the accumulation of intracellular Na ϩ that should activate K Na channels, thereby counterbalancing the alteration of membrane potential produced by activity of the Na ϩ /Ca 2ϩ pump.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that in circular smooth muscle of the opossum LES, the activation of K Na channels may serve to stabilize the RMP. The basal tone of the LES is maintained by constant Ca ϩ influx via ongoing Ca 2ϩ action potentials (34), and the accumulated Ca 2ϩ is likely extruded from the cell via a Na ϩ /Ca 2ϩ exchanger (25). This, in turn, leads to the accumulation of intracellular Na ϩ that should activate K Na channels, thereby counterbalancing the alteration of membrane potential produced by activity of the Na ϩ /Ca 2ϩ pump.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a role for Ca 2ϩ influx via L-type Ca 2ϩ channels was demonstrated in several animal models, including canine (Salapatek et al, 1998), feline (Muinuddin et al, 2004), and opossum (Zhang et al, 2000) LES. Our previous studies in human esophagus at both the tissue and cell levels revealed similar dependence on extracellular Ca 2ϩ (Kovac et al, 2005).…”
Section: Downloaded Frommentioning
confidence: 99%
“…These channels also participate in spontaneous contractions of smooth muscle in lower esophageal sphincter and myometrium [8,9]. In addition, Ca 2+ -activated Cl -channels, which are expressed in many cell types, are involved in signal transduction for diverse physiological functions such as membrane excitability, osmotic balance, transepithelial chloride movements, or fluid secretion [10].…”
Section: Introductionmentioning
confidence: 99%